2013
DOI: 10.1016/j.apmr.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Intervention Research Among Underserved Populations: Lessons Learned and Recommendations for Researchers

Abstract: Randomized controlled trials (RCTs) are considered the gold standard in research design for establishing treatment efficacy. However, the rigorous and highly controlled conditions of RCTs can be difficult to attain when conducting research among individuals living with a confluence of disability, low socioeconomic status, and being a member of a racial/ethnic minority group, who may be more likely to have unstable life circumstances. Research on effective interventions for these groups is urgently needed, as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…These strategies are similar to others reported in similar trials [8,1617] , and we believe they are essential to building trust between research staff, organizations, and participants. It was very apparent that the relationship between our academic setting and the research setting (i.e, Head Start programs, WIC ) needed to a cooperative partnership, especially in the school setting where our intervention did not address traditional academic content.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These strategies are similar to others reported in similar trials [8,1617] , and we believe they are essential to building trust between research staff, organizations, and participants. It was very apparent that the relationship between our academic setting and the research setting (i.e, Head Start programs, WIC ) needed to a cooperative partnership, especially in the school setting where our intervention did not address traditional academic content.…”
Section: Discussionsupporting
confidence: 74%
“…[3233] Higher loss to follow-up is a significant problem among low-income and minority populations due to transportation challenges, transient living situations, distrust of research, inconsistent contact information, and language barriers. [9,14,16] …”
Section: Discussionmentioning
confidence: 99%
“…those of low-socioeconomic status) attempt to quit at the same rate as others their success in quitting is lower 2 . This is leading to increasing disparities in smoking prevalence between the upper and lower social grades in the United Kingdom 3 , with similar trends being observed in the United States 4 , suggesting a need for interventions specifically designed for these groups 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The past research had success at increasing their involvement from lowincome populations, while they did not discuss major failures. Pyatak et al (2013) conducted a quantitative study about the challenges observed in a randomized control study, Redesign for Pressure Ulcer Prevention in Spinal Cord Injury. The study focused on a demographic of low socioeconomic status, ethnicity, and disability.…”
Section: Strategies To Increase Participant Involvementmentioning
confidence: 99%